Analysis of Technical Energy Losses By Using Simulation - Betrianis, Betrianis; Herawan, Randite (UI Scholars Hub, 2006)
Model is a representation of a system. Through model, it can be easier to forecast and control the changing of each element system. Electricity distribution is also a system. Losses are general problem that exist in a distribution network system. But with the right methods, specifically technical energy losses can be reduced in order to increase the efficiency. By making model of the distribution network, the value of technical energy losses in the whole network as well as in every line can be observed. Simulation can also be used to see all losses reduction alternatives. By comparing results from each alternatives, the best alternative, which gives best result can be decided and implemented.